Islamic Perspectives on Western Education - Sulaiman, Kamal-deen Olawale (INSANCITA, 2016)
ABSTRACT: Islam has, from its inception, placed a high premium on education and has enjoyed a long and rich intellectual tradition. The important of education is repeatedly emphasized in the Al-Qurâan, whether such knowledge is Islamic or Western education. Meanwhile, many people believed that Islam against Western education, because a significant number of people who are non-literate in Western education bear Muslim names. This paper, therefore, looks at the Islamic concept of education, its aims and objectives, history of Islamic education, and the contributions of early Muslims to the development of education. In Islamic educational theory, knowledge is gained in order to actualize and perfect all dimensions of the human being. From an Islamic perspective, the highest and most useful model of perfection is the Prophet Muhammad SAW (peace be upon him). In this context, its ultimate goal in education is the abode of permanence and all education points to the permanent world of eternity. The paper also traces the advent of Christianity/Western education that was dangerous for the Islamic education. Historically speaking, the West has borrowed a great deal of intellectual property from Arabs and Muslims in general. It also showed that the main purpose behind establishing Western Missionary schools was to plant poisonous seeds of polytheism and disbelief in the hearts of the Muslim children and deprive them of Islam, so that they might not remain as Muslims, even though they donât embrace Christianity. KEY WORD: Islamic Perspective on Education; Western Education; Muslim Contributions to West Civilization; History of Islamic Education.Â ABSTRAKSI: âPerspektif Islam tentang Pendidikan Baratâ. Islam, sedari awal, menempatkan posisi yang tinggi pada pendidikan dan telah menikmati tradisi intelektual yang panjang dan kaya. Pentingnya pendidikan berulang kali ditekankan dalam Al-Quran, apakah pengetahuan tersebut berasal dari pendidikan Islam atau Barat. Sementara itu, banyak orang percaya bahwa Islam bertentangan dengan pendidikan Barat, karena sejumlah besar orang yang tidak terdidik secara Barat menanggung nama Muslim. Makalah ini, dengan demikian, melihat konsep Islam tentang pendidikan, maksud dan tujuannya, sejarah pendidikan Islam, dan kontribusi Muslim awal untuk pengembangan pendidikan. Dalam teori pendidikan Islam, pengetahuan yang diperoleh dalam rangka aktualisasi diri dan menyempurnakan semua dimensi kehidupan manusia. Dari perspektif Islam pula, model tertinggi dan paling berguna dalam kesempurnaan hidup adalah Nabi Muhammad SAW (Salallahu Alaihi Wassalam). Dalam konteks ini, tujuan utama dalam pendidikan adalah tempat tinggal permanen dan semua titik tuju pendidikan adalah dunia kehidupan yang abadi. Makalah ini juga menjejaki kedatangan agama Kristen/pendidikan Barat yang berbahaya bagi pendidikan Islam. Secara historis berbicara, Barat telah meminjam banyak dari kekayaan intelektual dari Arab dan umat Islam pada umumnya. Hal ini juga menunjukan bahwa tujuan utama di balik mendirikan sekolah Misionaris Barat adalah untuk menanam benih beracun tentang kemusyrikan dan kekafiran di hati anak-anak Muslim dan menghalangi mereka dari Islam, sehingga mereka mungkin tidak tetap sebagai Muslim, meskipun mereka tidak memeluk agama Kristen.KATA KUNCI: Perspektif Islam tentang Pendidikan; Pendidikan Barat; Kontribusi Muslim terhadap Peradaban Barat; Sejarah Pendidikan Islam.About the Author: Kamal-deen Olawale Sulaiman, Ph.D. is a Senior Lecturer of Islamic Civilizations and Contemporary Islamic Studies at the Department of Religious Studies ESU (Ekiti-State University), Ado-Ekiti, Nigeria. For academic interests, the author is able to be contacted via phone: +2348068298472 or via e-mail: drsulaimanko@yahoo.comHow to cite this article? Sulaiman, Kamal-deen Olawale. (2016). âIslamic Perspectives on Western Educationâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(2), August, pp.185-198. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776. Chronicle of the article: Accepted (June 8, 2016); Revised (July 27, 2016); and Published (August 30, 2016).